Implementation of Law Number 4 of 2019 in the Independent Practice of Midwives - N, Ratni; Nur, Ijang Budiana (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
The profession of a midwife is someone who participates in a midwifery program regularly, structured and recognized by the state. A midwife is considered a professional health worker and is responsible for working with women during pregnancy, childbirth and breastfeeding. The purpose of this study was to determine the implementation of midwifery laws in the independent practice of midwives in the City of Tasikmalaya. The research method uses empirical with quantitative descriptive. This study used a sample of 40 respondents who owned and carried out midwifery independent practice. From the research results, it was found that all midwives already knew about midwifery laws and standards, and the sanctions received if practices did not comply with applicable standards. However, there are still 10% who have not extended STR and SIPB, as well as facilities and infrastructure that are not up to standard. It is hoped that there will be supervision and motivation for midwives to continue to maintain compliance in midwifery services. Keywords: Midwifery; Regulations; Midwife independent practice